Collaborative Governance and Stakeholder Dynamics in Improving the Quality of Life of Coastal Communities amidst the Coastal Waste Crisis in Bandar Lampung - Amantha, Goestyari Kurnia (Journal Public Policy, 2025)
This study aims to examine the condition of waste management on the Sukaraja Coast, Bumi Waras District, Bandar Lampung City and analyze the extent to which collaboration between stakeholders has been established in waste management efforts in the area. The method used is descriptive qualitative with data collection techniques through interviews and digital media sources. The results of the study indicate that the Sukaraja Coast faces a complex waste problem, caused by a combination of waste sent from rivers that flow into the coast and waste disposal activities by the surrounding community. Collaboration between stakeholders, especially between the Bandar Lampung City Government, Lampung Provincial Government, WALHI, and local communities, has not been effective. The absence of specific regulations governing collaboration mechanisms and the lack of ongoing commitment hinder the formation of effective joint governance. Mass beach clean-ups that have been carried out have only been able to create short-term impacts, because the root of the problem in the form of weak institutional design and low public awareness have not been seriously addressed. In conclusion, it is necessary to strengthen institutional design based on collaborative governance, increase the capacity of government institutions, and educate and empower coastal communities in a sustainable manner so that waste management on the Sukaraja Coast is more effective and has long-term impacts.